Analisis Deskriptif Hasil Belajar Mahasiswa Mata Kuliah Statistika - Rozana, Intan (Global Action and Education for Society, 2025)
Students’ final grades are still not satisfactory after the semester ends. Current data shows that the average final grade is below 70. Several factors are interrelated to shape students’ learning outcomes. The following factors contribute to the total: 20% for instructor observation, 25% for assignments, 25% for midterm exams, and 30% for final exams. In order to use the results of the Statistics course as a benchmark for future comparison courses, a descriptive study of the learning outcomes of the course is needed. The course can focus more on students’ strengths and areas for improvement if the instructor pays close attention to the stated course objectives. This study was conducted in the Information Systems Study Program of Bina Sarana Informatika University under the Faculty of Engineering and Informatics. The study will be conducted from September 2023 to February 2024. Participants in this study were all students enrolled in the Statistics course for the 2023–2024 academic year, namely third semester students. Students often get an A grade with a score range of 80-100 on the final exam based on lecturer observations, assignments, midterm grades, and final semester exams. Statistics scores can be used as a consideration for learning related courses. So that lecturers can anticipate low scores obtained by students.